Tracers for non-invasive radionuclide imaging of immune checkpoint expression in cancer - Peter Wierstra; Gerwin Sandker; Erik Aarntzen; Martin Gotthardt; Gosse Adema; Johan Bussink; René Raavé; Sandra Heskamp (EJNMMI Radiopharmacy and Chemistry, 2019)
Abstract Immunotherapy with checkpoint inhibitors demonstrates impressive improvements in the treatment of several types of cancer. Unfortunately, not all patients respond to therapy while severe immune-related adverse effects are prevalent. Currently, patient stratification is based on immunotherapy marker expression through immunohistochemical analysis on biopsied material. However, expression can be heterogeneous within and between tumor lesions, amplifying the sampling limitations of biopsies. Analysis of immunotherapy target expression by non-invasive quantitative molecular imaging with PET or SPECT may overcome this issue. In this review, an overview of tracers that have been developed for preclinical and clinical imaging of key immunotherapy targets, such as programmed cell death-1, programmed cell death ligand-1, IDO1 and cytotoxic T lymphocyte-associated antigen-4 is presented. We discuss important aspects to consider when developing such tracers and outline the future perspectives of molecular imaging of immunotherapy markers. Graphical abstract Current techniques in immune checkpoint imaging and its potential for future applications